Understanding Leadership Concepts in Enhancing the Quality of Islamic Education - Muhammad Rijal Achsanudin (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Islamic Education Management is a process of utilizing every facility owned by Islamic educational institutions, so that the quality of Islamic educational institutions needs to be continuously improved in accordance with the development of the times. This study aims to describe and analyze factors related to leadership management and improving the quality of Islamic education. The research method used is a literature study, namely conducting a review process on books, existing theories to be connected with the topic of leadership and quality of education, especially Islamic Education. The results of this study indicate that leadership and improving the quality of Islamic education as mandated by the national education goals require management that requires full support from various parties ranging from the government, school students, parents and the community. An improvement in the quality of education requires strengthening in several components, namely effective leadership, customer satisfaction, organizational culture, performance of educators and education personnel, curriculum and quality of graduates.